1981
DOI: 10.2466/pms.1981.53.3.723
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Types of Physical Fatigue on a Visual Detection Task

Abstract: The present study was designed to investigate the effects of different types of physical fatigue-past demand for exertion-on the performance of a visual detection task performed with and without masking. 31 male subjects were first administered a VO2 max test and familiarized with the detection task. They were divided into two groups to control potential effects of masking. They were subjected to three experimental treatment involving the utilization of different sources of energy: (a) a short anaerobic alacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 11 publications
0
17
1
1
Order By: Relevance
“…In fact, Hogervorst et al (1996) demonstrated a positive impact of IE on the subject cognitive performance, but it could be argued that their results could be caused by the expectancy of the subjects for a positive effect of exercise rather than on the intrinsic exercise effect. Whereas Grebot et al (2003) demonstrated that IE could increase the difficulty of recall shooting performance, Fleury et al (1981) could not detect any clear influence of IE on a letter-detection task.…”
Section: Discussionmentioning
confidence: 90%
“…In fact, Hogervorst et al (1996) demonstrated a positive impact of IE on the subject cognitive performance, but it could be argued that their results could be caused by the expectancy of the subjects for a positive effect of exercise rather than on the intrinsic exercise effect. Whereas Grebot et al (2003) demonstrated that IE could increase the difficulty of recall shooting performance, Fleury et al (1981) could not detect any clear influence of IE on a letter-detection task.…”
Section: Discussionmentioning
confidence: 90%
“…The lack of within-group differences in the experts certainly supports this notion. Second, Fleury and colleagues (Fleury, Bard, Jobin, & Carrière, 1981b) …”
Section: Discussionmentioning
confidence: 97%
“…For example typists, due to prolonged use of computers, experience more eye-related symptoms (27). These problems are prevalent in developed countries such as the US where more than 100 million people use computers on a daily basis and 50% of them experience eye-related problems (28). These problems include, eye strain, headaches, eye redness, dry eyes, burning eyes, weak vision, blurred vision, eye irritation, nervous tic, double vision, photophobia, nearsightedness, eye fatigue, light or glare sensitivity, watery eyes, contact lens discomfort, changes in color perception, etc.…”
Section: Discussionmentioning
confidence: 99%